Countering new(est) terrorism: hostage-taking, kidnapping, and active violence-assessing, negotiating, and assaulting - Newsome, Bruce Oliver (CRC Press/Taylor & Francis Group, 2018)
Introduction -- Analyzing new terrorist behaviors -- Assessing new terrorist risks -- Should you negotiate? -- Immediate management of the incident -- Develop a relationship -- Assess their psychology -- Assess their motivations, intentions, and goals -- Negotiating for ransoms -- Negotiating for prisoners -- Resolve the negotiation -- Should the official side consider violence? -- Assaulting